Mexican media art, ecologies, the posthuman, and politics - Pederson, Claudia Costa, author. Link
1 online resource.
Keywords: "This volume focuses on the connection between ecological thought and the technological arts in Mexico to challenge assumptions that ecological thought is a domain exclusive to the arts of the Global North and reconceive it as an inventive nexus of materialist speculations into a global posthuman world. Tracking the concept of ecology through a series of case studies taken from the histories of new media arts in Mexico over the last fifty years (from the mid-twentieth-century to the present), this book differs from ecological art histories that either ignore technological art or associate it exclusively with the global North. It includes artists and collectives working both in Mexico and transnationally and examines collaborative projects responding to anthropogenic environmental degradation in Mexico and elsewhere. The book will be of interest to scholars working in art history, Latin American studies, media studies, and environmental studies"--